RANCANG BANGUN TRAINER CUTTING TRANSMISI KOPLING BASAH: RANCANG BANGUN TRAINER CUTTING TRANSMISI KOPLING BASAH - Bahari, Ribut (Universitas Negeri Surabaya, 2020)
The purpose of this thesis is to create a Trainer Cutting Wet Coupling Transmission with a motorcycle machine which the capacity is 125cc and equipped with a roll support. This design uses engineering methods that include design ideas, study of literature, create designs, inventory components, manufacture tools, test tools, and conclusions.. Based on the table of general construction steel according to DIN 17100 (Sept. 1966) in terms of the tensile stress of the frame material (fmax) St 37 - 2 = 37.18 Kg / mm2 or 364.36 N mm2, with the safety factor (Sf) = 4, and the allowable tensile stress (fci) = fmax: Sf = 91,09N/mm2, because the bending stress is 48,60 N / mm2, the calculation result is smaller than the allowable tensile stress of the material which is 91,09N / mm2, the strength of the frame used is SAFE. Keyword: Wet Coupling, Manual Transmission, Chassis, Frame Strenght